The Effects of Solution-Focused Group Therapy in Treatment Outcomes and Psychological Well-Being of Substance Abuse Clients - Farhana Sabri; Melati Sumari; Marty Jencius; Jason McGlothlin (Human Resource Management Academic Research Society, 2024)
Non-Indexed Publication